2015
DOI: 10.1053/j.gastro.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Inflammatory Bowel Diseases

Abstract: In this Review, we provide an update on genome-wide association studies (GWAS) in inflammatory bowel disease (IBD). In addition, we summarize progress in defining the functional consequences of associated alleles for coding and non-coding genetic variation. In the small minority of loci where major association signals correspond to non-synonymous variation, we summarize studies defining their functional effects and implications for therapeutic targeting. Importantly, the large majority of GWAS-associated loci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
276
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 327 publications
(286 citation statements)
references
References 112 publications
4
276
0
6
Order By: Relevance
“…While it is possible that the sample size was too small to detect a correlation, it is also possible that additional genes involved in the development of CD in these patients also affect the development of Type I Paneth cell phenotype. Compared to adult CD, genetics plays a more important pathogenic role in pediatric CD, in particular those with very early onset disease (42)(43)(44), although in mouse models the Paneth cell antimicrobial function is independent of Nod2 (45). Thus, it is possible that additional CD susceptibility genes may cause the Paneth cell defect.…”
Section: Discussionmentioning
confidence: 99%
“…While it is possible that the sample size was too small to detect a correlation, it is also possible that additional genes involved in the development of CD in these patients also affect the development of Type I Paneth cell phenotype. Compared to adult CD, genetics plays a more important pathogenic role in pediatric CD, in particular those with very early onset disease (42)(43)(44), although in mouse models the Paneth cell antimicrobial function is independent of Nod2 (45). Thus, it is possible that additional CD susceptibility genes may cause the Paneth cell defect.…”
Section: Discussionmentioning
confidence: 99%
“…The exact causes of this disease remains unknown, but studies have proposed that it may be the result of complex interactions between multiple factors, such as genetic, environmental and immunological factors (8,9). There is direct evidence for the role of genetics in IBD, associated with the family history of patients, as well as increased rates of IBD in monozygotic twins (10,11). The predominant genetic association in IBD is divided into genes that contribute to innate and adaptive immune responses (12).…”
Section: Introductionmentioning
confidence: 99%
“…Genotype contributes to CD pathogenesis 35 and in addition the composition of the gut microbiota is partly determined by genotype. 36 In our study we demonstrated that genotype relative risk (a composite score of genotypic risk across 72 loci associated with CD) was the most significant factor in explaining variance between the 3 cohorts, (patients, healthy siblings and healthy, unrelated controls) and also within each cohort.…”
mentioning
confidence: 99%